Between Scylla and Charybdis: thrombosis in children with hemophilia - El Maamari, Jad; Amid, Ali; Pelland-Marcotte, Marie-Claude; Tole, Soumitra (Frontiers in Pediatrics, 2023)
Thromboembolism is an infrequent complication in children with hemophilia that has been traditionally associated with the presence of a central venous access device. Novel rebalancing agents have shown promising results as prophylactic therapies to minimize the risk of bleeding but both thromboembolism and thrombotic microangiopathy have been reported as complications. The management of thrombosis in children with hemophilia is particularly challenging given the inherent risk of bleeding. In this paper, we present clinical vignettes to review the literature, highlight challenges, and describe our approach to managing thromboembolism in children with hemophilia.